Pengaruh Komunikasi Interpersonal Dan Kepercayaan Terhadap Loyalitas Guru SMK Swasta Di Kecamatan Kemayoran Jakarta Pusat - Gilang Kartika Hanum (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
This research is aimed to investigate the effect of (1) interpersonal communication, (2) trust, (3) loyalty of teacher the vocational high school in Kemayoran.In the data analysis, this research uses causal survey method by using Path Analysis Technique. This study uses the sample from 95 teachers in five vocational high school in Kemayoran who are selected by using Slovin formula.The result of the study reveals that: First, there is a positive effect between interpersonal communication and teacher loyalty to the school. Second, there is a positive effect also between trust and teacher loyalty to the school.Third there is a positive effect between interpersonal communication and teacher trust to the school.